MAXILLARY SINUS LIFT: COMPARISON BETWEEN THE LATERAL WINDOW TECHNIQUE AND THE TRANSCRESTAL TECHNIQUE - Cruz, Roberto Machado; Vitale, Marcelo; Costa, Patrícia de Hollanda Cavalcanti Aragão; Souza, Micaell da Silva; Batista, Cristiane Elisa Ribas; do Nascimento, Caio Uriel Vinhote; Bento, Julia de Araújo Koplowitz; Silva, Matheus Rodrigues Serafim; Batista, Priscila Pereira; Ferreira, Douglas José de Araújo; Daleffe, Giovanni; Andrade, Theodoro Ribeiro; et al. (Seven Editora, 2026)
Maxillary sinus lift is a widely used procedure to enable dental implant placement in the posterior maxilla in cases of reduced bone height. Among the available techniques, the lateral window approach and the transcrestal technique stand out, presenting differences regarding invasiveness, bone gain, and postoperative morbidity. This study aimed to perform an integrative literature review comparing these two techniques in terms of indications, advantages, limitations, and clinical outcomes. The search was conducted in PubMed, SciELO, and ScienceDirect databases using specific descriptors combined with Boolean operators. Clinical studies, randomized trials, systematic reviews, and observational studies published between 2012 and 2025 were included. The results showed that both techniques present high implant survival and success rates. The lateral window technique demonstrated superior bone gain, especially in cases of severe atrophy, whereas the transcrestal technique showed lower morbidity and greater patient comfort. It is concluded that the choice of technique should be individualized, considering anatomical factors, residual bone height, and case complexity.